Ecological engineering: an assessment of the ecological impact of Reno mattress structures used in erosion control in the Keurbooms Estuary, South Africa - De Villiers, Nina (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2020)
Global climate changes have been associated with ocean warming and sea-level rise. Armouring of coastlines has become common practice with the increasing threat of coastal erosion. The transformation of soft sediment habitats to hard, artificial habitats because of coastline armouring can lead to changes in species diversity, composition and distribution. It is, therefore, essential to assess changes to habitats from coastal development as well as the ecological impact erosion control structures have within coastal systems. Ecological engineering attempts to combine engineering principals and ecological processes to reduce environmental impacts from coastal development and the implementation of artificial structures. Estuaries are particularly vulnerable to anthropogenic impacts through development, and are extremely important systems offering nursery and foraging grounds for many species. These systems are, however, particularly vulnerable to anthropogenic impacts from urbanisation and development. Within South Africa many estuaries are being transformed by the addition of artificial structures to combat erosion, one such structure is the Reno mattress (a flattened wire box filled with rocks). This study compared the fish diversity and abundances of existing Reno mattress structures and natural eelgrass (Zostera capensis) habitat in the Keurbooms Estuary, South Africa. Benthic invertebrates were sampled using standard core sampling and an adapted suction sampling approach within the two habitats. The non-destructive method of mini Baited Remote Underwater Video Systems (BRUVs) was used to sample fish. Seasonal benthic invertebrate and fish abundances and assemblages were assessed from winter 2018 to spring 2019 with greater abundances of both recorded in summer. Significantly greater abundances, diversity, and richness of fish were found in the Reno mattress habitat compared to Z. capensis. Invertebrate taxa displayed some overlap between habitats, however, three higher taxonomic groups were only recorded within Reno mattress habitat and one only within the eelgrass habitat. Fish assemblages differed significantly between the two established habitats. A Before-After-Control-Impact (BACI) investigation was used to assess the ecological impact of newly installed Reno mattresses in the Keurbooms Estuary. Zostera capensis extent was sampled by determining the percentage cover of 0.5 m X 0.5 m quadrats and measurements of eelgrass blades. Percentage cover and blade length decreased during the installation of Reno mattress, but then recovered shortly after completion of the installation. Abundances, richness and diversity of invertebrates and fish were found to be similar before and after the installation which suggests that the installation had no net negative impact on the site. The Reno mattresses were found to attract fauna typical of rocky shore environments as well as a few invasive alien invertebrate species. This study noted that a hybrid habitat of Reno mattress and eelgrass was created and may in fact provide the positives of both to a system. In any coastal development it will be important to balance the demands of a growing population and the protection of natural habitats. The results of this study suggest that complex artificial structures such as Reno mattresses do provide habitat for fish and invertebrates. However, the use of these structures should be in combination with natural vegetation (e.g. as a hybrid habitat) and not one that replaces intertidal and subtidal natural habitat especially eelgrass. There is limited information regarding the ecological impacts of using Reno mattresses in estuaries and this study provides new information on their ecological efficacy that should be valuable for future coastal erosion control practices.
Keywords: Sediments (Geology) -- Management; Sediments (Geology) -- South Africa -- Keurboomstrand; Coast changes -- South Africa -- Keurboomstrand; Shore protection -- South Africa -- Keurboomstrand; Coastal engineering-- -- South Africa -- Keurboomstrand; Coastal zone management-- -- South Africa -- Keurboomstrand; Estuarine ecology-- -- South Africa -- Keurboomstrand; Eelgrass -- South Africa -- Keurboomstrand; Reno Mattresses